MARK TWAIN IN THE RUSSIAN PERIODICALS. Part 1 - Ekaterina A. Stetsenko (Studia Litterarum)
This article deals with the interpretation of the works by Mark Twain, famous Ame- This article deals with the interpretation of the works by Mark Twain, famous American author, in the Russian pre-revolutionary periodical press (1872–1916). The objects of research are critical articles, essays, reviews, correspondences, introductions to publica tions of Twain’s short stories and novels, obituaries, and other materials printed in central and provincial magazines and newspapers. Perception of Twain in Russia was contingent on many factors including political and cultural situation in the country, state of social thought and literary criticism, newspaper and magazine conjuncture etc., always remain ing polysemantic and conflicting. In different times, in the years of democratic rising or reaction critics looked for something in Twain’s works that corresponded to the spirit of their time and helped solve ideological and aesthetic problems. Twain had reputation of either a “pure humorist” or a great writer, philosopher, and moralist. Democrats, liberals, conservatives, feminists, adepts of realistic or naturalistic trends in art discussed Twain’s works that became a source of knowledge about the United States and inspired polemics about Russia’s further development. Twain was highly esteemed as the author of books for children and young people. Yet his works that criticized monarchism and imperialism were often ignored or abridged. The history of Twain’s interpretation in the Russian press serves as evidence of the fact that perception of foreign literature is a dynamic and bumpy pro cess, repeating itself and moving backwards but also getting to deeper levels of meanings.